Peculiarities of the effect of zinc chelate on prooxidant-antioxidant homeosta-sis in the blood of sows and their relationship with the reproductive capacity - I. V. Sarnavska (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки, 2024)
During the last decades, research has been actively conducted to increase the reproductive capacity of sows. It was determined that during puberty, the sow’s body actively assimilates nutrients that should provide for their own needs and embryos and creates a reserve for the lactation period. The study aimed to determine the influence of zinc in the form of chelate on the state of prooxidant-antioxidant homeostasis on the reproductive capacity of sows. In the experiment, 45 heads of the Large White breed sows were used, and they were selected and divided into groups (5 heads each) according to the principle of analogs. The norms fed barren and farrowing sows according to their physiological state. The diet of the control group of sows from sexual rest to the 28th day of farrowing remained unchanged; the 1st experimental group – MD+5 % Zinc in the form of zinc chelate, the II experimental group – MD+10 % Zinc in the form of Zinc chelate. Additional feeding of biologically active compounds was stopped one day before farrowing. During the phase of sexual rest, estrus, on the 90th and 104th days of farrowing, the day of farrowing, as well as on the 5th and 28th days of the suckling period, blood was taken from sows and their piglets to determine the state of PAH. It has been determined that in the blood of sows, the periods of the reproductive cycle determine the peculiarities of the formation of prooxidant-antioxidant homeostasis. In particular, during estrus, there is an intensification of peroxide oxidation processes – the content of diene conjugates increases by 56.9 %, TBC-active compounds by 12.3 %, and the level of low molecular weight antioxidants – reduced glutathione decreases (Р < 0.001). This is accompanied by a significant increase in the activities of antioxidant enzymes – superoxide dismutase (Р < 0.05) and catalase (Р < 0.05). It was found that the intensification of peroxide oxidation processes is intensified on the day of farrowing of sows – the content of diene conjugates increases by 26.6 % and TBC-active compounds by 31.8 % with a further decrease during lactation to the level of sexual rest. Animals that received zinc in the form of zinc chelate 5 % above the norm were characterized by a lower intensity of peroxide oxidation processes. Additional feeding of zinc in the form of zinc chelate to sows by 10 % more than the norm is accompanied by a decrease in fertility (Р < 0.05), the number of live piglets (Р < 0.05), litter weight at birth by 10.0 % and litter weight at weaning – 11.6 %. Sows that received this feed supplement of microelement 5 % above the norm are characterized by higher fertility by 4 % and litter weight at birth by 4.2 %.